Virus receptor interaction in the adenovirus system. II. Capping and cooperative binding of virions on HeLa cells. - Persson, R (1983)
Adenovirus type 2 attachment to HeLa cells was analyzed under controlled conditions. The temperature-dependent attachment kinetics revealed an inflection point at around 20 degrees C, and above this temperature the increase of the rate was doubled. In multiplicity dependence experiments, the attachment exhibited positive cooperative binding at 37 degrees C. This binding pattern was inhibited by low temperatures and prefixation of cells with 0.015% glutaraldehyde. Attachment of rhodamine-labeled virions revealed capping of the particles on 15% of the cells at 37 degrees C. Capping was inhibited by low temperatures, glutaraldehyde fixation of cells, and treatment with cytochalasin B, azide, and 2-deoxyglucose. Consequently, we propose that the adenovirus type 2 attachment to cells leads to rearrangements in the plasma membrane, resulting in cooperative binding and capping of the virus particles.